Handbook Guideline for Writing Research Articles in Social Sciences for Academic Journals - Rikharom, Rujira (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
The objectives of this research article were to: 1) analyze the writing patterns of social science research articles from the national level, Group 1, and ASEAN regional level academic journals in Thailand; 2) develop a template for writing social science research articles in academic journals, and 3) evaluate the quality and endorse the template for writing social science research articles in academic journals. A Mixed-methods research that utilized qualitative research through document analysis. The data collection using purposive sampling were 30 social science journals accredited for quality and included in the Thai Journal Citation Index Center database, round 4, for 2020-2024. The data was collected by searching the journal websites and using a data collection form. The data analysis categorizes and structures the main themes and topics. For quantitative research, a quality assessment and validation of the data collection instrument were conducted with a simple random of 15 participants through an online platform. The data were analyzed using descriptive statistics to determine the mean and standard deviation and present the findings of the descriptive analytics. Results indicated that: 1) the format of research articles consisted of important components, including the title, authors’ names, abstract, keywords, introduction, research objectives, research methodology, research findings, discussion, recommendations, and references; 2) the research article writing manual which related to the research article format; introduction section, detailed section, and conclusion section; 3) overall, the manual prototype was the high qualified level (X=4.32, S.D.=0.65, X=4.35, S.D.=0.61). The analysis results of the manual prototype showed that design methods, creation of procedures, processes, and recommendations for writing social science research articles based on the systematic analysis and explanation of data would help writing clearly and concisely.